Serum Uric Acid: A Novel Risk Factor for Gestational Diabetes Mellitus - Singh, Urmila; Mehrotra, Seema; Singh, Renu; Sujata, Sujata; Gangwar, Madhu Lata; Shukla, Bhumika (International Journal of Medical Research and Review, 2015)
Introduction: To analyze the relationship between first trimester uric acid levels and risk of development of gestational diabetes mellitus (GDM). Method: A total of 300 pregnant women up to 14 weeks of pregnancy were enrolled in this study. After obtaining their demographic data and clinical assessment blood sample for serum uric acid was taken. Women were subsequently followed till term. All women were subjected to blood sugar screening one hour after 50 gm glucose and glucose tolerance test if screening was < 200mg/dl. GDM was diagnosed by 3 hours glucose tolerance test using Carpenter and Coustan criteria or by one hour screening value > 200 mg /dl. Results: GDM complicated 2.66% (8/300) of the pregnancies. All the women with serum uric acid > 5 mg/dl (n=6) had deranged blood sugar screening and out of this 5 developed GDM. Conclusion: The study demonstrates a striking association between first trimester uric acid and risk of developing GDM. First trimester uric acid level may be used as predictor for development of GDM.